2019
DOI: 10.5694/mja2.50425
|View full text |Cite
|
Sign up to set email alerts
|

Second primary cancers in people who had cancer as children: an Australian Childhood Cancer Registry population‐based study

Abstract: Objective To investigate the incidence of second primary cancers in people diagnosed with cancer during childhood. Design, setting Retrospective, population‐based study; analysis of Australian Childhood Cancer Registry data. Participants People alive at least two months after being diagnosed before the age of 15 years with a primary cancer, 1983–2013, followed until 31 December 2015 (2–33 years' follow‐up). Main outcome measures Risks of second primary cancer compared with the general population, expressed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…It is therefore a privilege to announce the top articles published by the MJA in 2020 as chosen by the editors. [13][14][15][16][17][18][19][20][21][22][23] The MJA published leading research and perspectives on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including the first SARS-CoV-2 isolated in Australia, uploaded to GenBank for immediate sharing with the global scientific community. 13 On 19 January 2020, a man from Wuhan was admitted in a hospital due to progressive respiratory symptoms 5 days after arrival in Melbourne.…”
Section: Editorialsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore a privilege to announce the top articles published by the MJA in 2020 as chosen by the editors. [13][14][15][16][17][18][19][20][21][22][23] The MJA published leading research and perspectives on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including the first SARS-CoV-2 isolated in Australia, uploaded to GenBank for immediate sharing with the global scientific community. 13 On 19 January 2020, a man from Wuhan was admitted in a hospital due to progressive respiratory symptoms 5 days after arrival in Melbourne.…”
Section: Editorialsmentioning
confidence: 99%
“…Paediatric cancers are increasing in Australia and new evidence about outcomes were highlighted in two important research articles. 21,22 An analysis of data from the Australian Childhood Cancer Registry by Youlden and colleagues 21 found that, having been stable between 1996 and 2005, the overall incidence of childhood cancers rose by 1.2% per year between 2005 and 2015. Further, the authors conservatively estimated that the incidence rate of childhood cancers would increase by 7% over the next 20 years.…”
Section: Editorialsmentioning
confidence: 99%
See 2 more Smart Citations
“…As survival rates improve for children and young adults with cancer, there is emerging awareness of the pervading physical, emotional and psychological tolls on survivors of a childhood cancer diagnosis and treatment. Two‐thirds of patients with childhood cancers have significant long term treatment side effects, including organ dysfunction, neurocognitive deficits, impaired fertility, and secondary malignancies . The impact of the late sequelae of childhood cancer and treatment is extremely significant and it is imperative that efforts to minimise late effects continue, as well as providing services that meet the physical, emotional and psychological needs of survivors …”
mentioning
confidence: 99%